Producing and Using Organic NPK Fertilizer From Agricultural and Household Waste by a Farmer Group in Sleman, Yogyakarta - Sudaryatno, Sudaryatno; Prasetya, Agus; Sulaiman, Muhammad; Sartika, Heni Wahyu; Santoso, Dian Hudawan; Bato, Marjan; Fadliyah, Nurul; Maliga, Iga; Kisnanto, Indro (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
The agricultural industry, including the cultivation of paddy and vegetables, plays a crucial role in the economy of Padukuhan Dukuh and serves as its residents' primary source of income. Nevertheless, farmers have expressed that the challenge of acquiring subsidized fertilizers from the government substantially hinders the agricultural process. Compound fertilizer, often known as NPK fertilizer, is a specific chemical fertilizer frequently used by farmers to enhance soil fertility rapidly. This community service program aims to spread awareness about using alternative fertilizers (such as compost and liquid organic NPK) to minimize the adverse effects of fertilization on the environment. Additionally, the program seeks to promote the conversion of agricultural and household waste into organic fertilizers. The service activity took place from September 10 to October 14, 2023. Padukuhan Dukuh is the location where the production of alternative organic fertilizers using agricultural and home waste takes place. This service aims to offer support to the members of the "Ngudi Makmur" Farmer Group, located in Padukuhan Dukuh, Sinduharjo, Ngaglik, Sleman, DIY. There were 20 members of the farmer group present at the service. The community service stages are categorized into various implementation methodologies, specifically knowledge sharing, a workshop, monitoring, and evaluation. The results have been collected, and a favorable response from the community has been received. This offers a unique organic NPK fertilizer that is readily available and more efficient. The program has been assessed from various perspectives, including its sustainability. Several aspects must be taken into account to evaluate the program's sustainability. These factors encompass the necessity to enhance the caliber of human resources, augment crop output, maintain the reliability of fertilizer production via compost houses, and consider the economic and socio-cultural values.